IMPLEMENTASI ASPEK RELIGIUS DALAM KURIKULUM JABAR MASAGI DI SMAN 6 BANDUNG - Khansa Azzahra Yasa, - (2021)
Jabar Masagi curriculum is a model of implementing a national curriculum based on local cultural values with 4 aspects, namely love of religion, defending the country, caring for the environment and love of culture. In general, this study aims to describe how the religious aspects of Jabar Masagi at SMAN 6 Bandung, specifically this study aims to: (1) describe the implementation of the Jabar Masagi curriculum at SMAN 6 Bandung; (2) Describe the habituation of religious aspects in the Jabar Masagi curriculum at SMAN 6 Bandung; (3) Describe the impact that occurs on students in the implementation of religious aspects in the Jabar Masagi curriculum at SMAN 6 Bandung; (4) Describe the obstacles that occur in the implementation of religious aspects in the Jabar Masagi curriculum at SMAN 6 Bandung. This study uses a qualitative descriptive method. Collecting data using interview techniques and document studies. Data analysis was carried out by means of data reduction, data display, and data verification. The results showed that the implementation of the religious aspect in the Jabar Masagi curriculum had been carried out through moral development activities, habituation of the Duha prayer, the habit of reading the Qur'an every day and the Program Qiro'at. Constraints that occur in the implementation of the religious aspect in the Jabar Masagi curriculum at SMAN 6 Bandung, namely the implementation of online schools caused by the COVID-19 pandemic, the implementation of the religious aspect in the Jabar Masagi curriculum has limitations. In addition, the implementation of moral development has not been evenly distributed to students so that there are still students who have not felt the impact that occurred in the implementation of the implementation of religious aspects in the Jabar Masagi curriculum at SMAN 6 Bandung.